2014
DOI: 10.1186/1471-2474-15-144
|View full text |Cite
|
Sign up to set email alerts
|

Association of LRP5 genotypes with osteoporosis in Tunisian post-menopausal women

Abstract: BackgroundOsteoporosis is a highly heritable trait. Among the genes associated with bone mineral density (BMD), the low-density lipoprotein receptor-related protein 5 gene (LRP5) has been consistently identified in Caucasians. However LRP5 contribution to osteoporosis in populations of other ethnicities remains poorly known.MethodsTo determine whether LRP5 polymorphisms Ala1330Val and Val667Met are associated with BMD in North Africans, these genotypes were analyzed in 566 post-menopausal Tunisian women with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
0
11
1
Order By: Relevance
“…They discussed that this was aligned with other researchers finding where they determined association of A1330V with lumbar spine BMD in Asians. However, in Caucasian populations the association was observed in both spine and femoral neck BMD [58]. Park SE et al (2014) found an association with LRP5 rs599083 and femoral neck BMD in Korean men [59].…”
Section: Lrp Mutations In Bone Related Diseasesmentioning
confidence: 99%
“…They discussed that this was aligned with other researchers finding where they determined association of A1330V with lumbar spine BMD in Asians. However, in Caucasian populations the association was observed in both spine and femoral neck BMD [58]. Park SE et al (2014) found an association with LRP5 rs599083 and femoral neck BMD in Korean men [59].…”
Section: Lrp Mutations In Bone Related Diseasesmentioning
confidence: 99%
“…Recently, a number of polymorphisms have been described in the LRP5 gene (http://www.ncbi.nlm.nih.gov/SNP). Among them, the Ala1330Val (rs3736228, exon 18) polymorphism has been studied most extensively (van Meurs et al, 2008) and was found to affect bone mineral density (Sassi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Significant associations were seen with seven SNPs, one of them is VDR SNP rs731246. In consistency, analysis of LRP5 polymorphisms in postmenopausal North African (Tunisian) women showed no association with BMD at any sites [48].…”
Section: Non-modifiable Risk Factors Modifiable Risk Factorsmentioning
confidence: 86%